Current Status and Issues Concerning Magnetic Resonance Imaging in Patients with a Magnetic Resonance Conditional Cardiac Implantable Electrical Device: A Single-center Study - Ikeya, Yukitoshi (Intern Med, 2021)
OBJECTIVE: Following the introduction of magnetic resonance (MR)-conditional cardiac implantable electrical devices (CIEDs), patients with CIEDs have undergone MRI scanning more frequently. As the required settings of MRI equipment for scanning patients with a CIED vary by device, a number of precautions should be taken to allow safe examinations, including the confirmation of conditions and selection of MRI modes appropriate for pacing status in individual patients. In this study, we examined the current status and issues concerning the performance of MRI examinations in patients with an MRI-conditional CIED. METHOD AND RESULTS: We reviewed a total of 262 MRI scans. The most common site of MRI scanning was the head, followed by the spine, abdomen, and heart in order. Regarding the MRI mode, DOO was most often used, followed by OFF, AOO, and finally VOO mode, to maintain atrioventricular synchrony. Although no obvious adverse events were observed related to MRI scanning, there were several cases encountered that might have been predisposed to a significant incident or in which the patient's intrinsic pulse rates or subjective symptoms changed before and during scanning. CONCLUSION: As MRI is a very useful diagnostic tool for cerebrovascular diseases and orthopedic disorders, the demand for MRI scanning is high when treating these areas. Although MRI scanning in patients with MR-conditional devices was performed without any adverse events, there were incidents that could have potentially led to major harm. This highlights the importance of confirming the appropriate MRI mode is being used before scanning and monitoring patients during scanning.